Transient thermal characteristics related to catastrophic optical damage in high power AlGaAs/GaAs laser diodes. Issue 11 (12th August 2013) - Qiao, Yanbin; Feng, Shiwei; Xiong, Cong; Zhu, Hui; Ma, Xiaoyu; Yue, Yuan
<x xml:space="preserve">Abstract</x> The transient thermal characteristics related to catastrophic optical damage (COD) in high power AlGaAs/GaAs laser diodes (LDs) are studied experimentally by means of thermal infrared imaging, laser scanning confocal microscopy, and transient thermal technique. The transient thermal technique is based on the diode forward voltage method in which the structure function theory is applied to determine the component thermal resistance and temperature rise of the LDs. We have recorded the dynamics of COD process using thermal infrared camera. Two melting spots are observed in the output facet after COD which location exactly matches the position of the thermal flash from the thermal imaging and even the temperature of COD seed has a sudden increase of 32 K when the COD event occurs. Furthermore, we find that the thermal resistance from chip to In solder increases remarkably after COD, meanwhile the thermal resistance of solder and package does not change apparently. The results are attributed to the heat power dissipation increase originating from the enhancement of nonradiative recombination after COD under constant input electrical power.